Carcinoma de paratiróide - Vieira, José Gilberto H. [UNIFESP] (2005)
Parathyroid carcinoma is a rare condition, comprising less than 1% of the cases of primary hyperparathyroidism (PHP). Nonetheless, due to its aggressiveness, and having prognosis dependent on the precocity of diagnosis and radical therapeutic approach, it is paramount that the clinical suspicion be made before surgery. Clinical presentation is typical of severe PHP, with a parathyroid tumor >1.5cm, usually palpable. The pathologic features sometimes are difficult to characterize. Our experience with this condition (from 1983 to 2004) includes 7 cases, all symptomatic, hypercalcemic syndrome and bone disease present in most of them. In 6/7 the tumor was palpable, and in all the biochemical profile was compatible with severe PHP. Three patients died of complications of hypercalcemia. Recent findings point to a mutation on the gene HRPT2 as the molecular base for the development of this kind of tumor. The therapeutic approach is surgical and should include ipsilateral thyroidectomy and cervical exploration in order to find possible local metastasis. Post-surgical complications (mainly hypocalcemia) are proportional to the pre-existing metabolic alterations. The long-term prognosis depends upon the precocity of diagnosis, surgical success and control of hypercalcemia. New therapeutic approaches, based on bisphosphonates and calcimimetic drugs, as well as the possibility of genetic diagnosis, tend to ameliorate the prognosis of this severe affection.